Long-term survival following in-hospital cardiac arrest: A matched cohort study. (February 2016) - Feingold, Paul L.; Mina, Michael J.; Burke, Rachel M.; Hashimoto, Barry; Gregg, Sara; Martin, Greg S.; Leeper, Kenneth; Buchman, Timothy
Abstract: Background: Each year, 200, 000 patients undergo an in-hospital cardiac arrest (IHCA), with approximately 15–20% surviving to discharge. Little is known, however, about the long-term prognosis of these patients after discharge. Previous efforts to describe out-of-hospital survival of IHCA patients have been limited by small sample sizes and narrow patient populations Methods: A single institution matched cohort study was undertaken to describe mortality following IHCA. Patients surviving to discharge following an IHCA between 2008 and 2010 were matched on age, sex, race and hospital admission criteria with non-IHCA hospital controls and follow-up between 9 and 45 months. Kaplan–Meier curves and Cox PH models assessed differences in survival. Results: Of the 1262 IHCAs, 20% survived to hospital discharge. Of those discharged, survival at 1 year post-discharge was 59% for IHCA patients and 82% for controls ( p < 0.0001). Hazard ratios (IHCA vs. controls) for mortality were greatest within the 90 days following discharge (HR = 2.90, p < 0.0001) and decreased linearly thereafter, with those surviving to one year post-discharge having an HR for mortality below 1.0. Survival after discharge varied amongst IHCA survivors. When grouped by discharge destination, out of hospital survival varied; in fact, IHCA patients discharged home without services demonstrated no survival difference compared to their non-IHCA controls (HR 1.10, p = 0.72). IHCA patients discharged to long-term hospital care or hospice, however, had a significantly higher mortality compared to matched controls (HR 3.91 and 20.3, respectively; p < 0.0001). Conclusion: Among IHCA patients who survive to hospital discharge, the highest risk of death is within the first 90 days after discharge. Additionally, IHCA survivors overall have increased long-term mortality vs. controls. Survival rates were varied widely with different discharge destinations, and those discharged to home, skilled nursing facilities or to rehabilitation services had survival rates no different than controls. Thus, increased mortality was primarily driven by patients discharged to long-term care or hospice.